2017
DOI: 10.1038/jp.2017.88
|View full text |Cite
|
Sign up to set email alerts
|

Reduced narcotic and sedative utilization in a NICU after implementation of pain management guidelines

Abstract: Evidence-based guidelines led to significant reduction in opioids and sedatives exposure, and in the number of infants requiring methadone for iatrogenic narcotic dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 48 publications
1
34
0
1
Order By: Relevance
“…In the EUROPAIN study, paracetamol prescription (14%) was more common than that of sedatives/hypnotics (12%) but still lower when compared to opioid exposure (26%). Besides the guidelinedriven decrease in morphine use as mentioned earlier and the increased paracetamol prescription of Rana et al, there is another recent paper on a clinical guideline-driven impact of reduced exposure to morphine and increased use of paracetamol (21,24). Baarslag et al reported that the adherence to a protocol that subsequently implemented intravenous paracetamol as a firstline treatment of pain after a major non-cardiac surgery in neonates and infants resulted in low (add-on) morphine needs, similar to the extent as published in the initial placebo-controlled randomized trial on the effect of intravenous paracetamol on post-operative morphine exposure (24,25).…”
Section: Epidemiology Of Drug Prescription Practices Of Analgesics Inmentioning
confidence: 92%
See 3 more Smart Citations
“…In the EUROPAIN study, paracetamol prescription (14%) was more common than that of sedatives/hypnotics (12%) but still lower when compared to opioid exposure (26%). Besides the guidelinedriven decrease in morphine use as mentioned earlier and the increased paracetamol prescription of Rana et al, there is another recent paper on a clinical guideline-driven impact of reduced exposure to morphine and increased use of paracetamol (21,24). Baarslag et al reported that the adherence to a protocol that subsequently implemented intravenous paracetamol as a firstline treatment of pain after a major non-cardiac surgery in neonates and infants resulted in low (add-on) morphine needs, similar to the extent as published in the initial placebo-controlled randomized trial on the effect of intravenous paracetamol on post-operative morphine exposure (24,25).…”
Section: Epidemiology Of Drug Prescription Practices Of Analgesics Inmentioning
confidence: 92%
“…In contrast, Simons et al (morphine maintenance infusion, 10 µg/kg/h) did not observe lower blood pressure in morphine-exposed preterm neonates nor in inotropic prescription practices, irrespective of the post-menstrual age, within their randomized, placebocontrolled study (12). Finally, morphine delayed the attainment of full enteral nutrition (secondary analysis) by 3 days [17 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) in the placebo arm compared to 20 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) days in the morphine arm] in the NEOPAIN trial (13).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Implementation exercises of guidelines on opioid use are effective to reduce the utilization of these drugs and its variability [ 26 ]. This reduction in exposure was reflected in the number of patients (from 63% to 33%) and the cumulative morphine dose (from 1.64 to 0.51 mg/kg, −68%).…”
Section: Neonatal Clinical Pharmacologymentioning
confidence: 99%